To Be or Not to Be a (Dead) Father. (14th September 2017) - Aristodemou, Maria
ABSTRACT: This article argues that Hamlet's tragedy shows the idiosyncratic intervention of the law in the creation of human subjectivity, an intervention that relies on the agency of a (dead) father to regulate the subject's desire. Hamlet's tragedy, it suggests, is characteristically modern not because Hamlet unconsciously desired to do what Oedipus consciously did, but because of the added ingredient of Hamlet's, and of the father's, knowledge: Hamlet not only knows of the father's death, he also knows that the father knows. In Hamlet the prior father, the father of Totem and Taboo, is reincarnated in the person of Claudius so the 'progress' from Oedipus to Hamlet, is from tragedy to obscenity. The Crown as phallus is called upon to conceal the obscenity but Hamlet, like any good analyst, plays and displays language to reveal the rotten crime at the heart of the State of Denmark and of the Law.